Impact of sintering temperature on the structural, morphological, and dielectric properties of (1-x)LaFeO3–xBaTiO3 (x = 0.49) - Amina Maou; Najwa Gouitaa; Fatima Zahra Ahjyaje; Taj Dine Lamcharfi; Farid Abdi; Noureddine Idrissi Kandri (Heliyon)
Solid solutions of (1-x)LaFeO₃-xBaTiO₃ with x = 0.49 were successfully synthesized via the conventional solid-state reaction method, focusing on the systematic evaluation of their structural, morphological, and dielectric properties under varying sintering conditions.X-ray diffraction (XRD) analysis coupled with advanced Rietveld refinement techniques confirmed the coexistence of orthorhombic (Pbnm) and tetragonal (P4mm) phases. The impact of sintering temperatures at 1200 °C, 1300 °C, and 1400 °C was evaluated in detail, revealing a significant increase in crystallite size from 3.062 μm to 8.667 μm with higher temperatures. Structural stability was confirmed through electron density mapping, which also provided valuable insights into the bonding characteristics of 0.51LFO-0.49BTO. This analysis underscores the pivotal role of thermal conditions in enhancing the material's phase stability, microstructural properties, and electrical performance, particularly in relation to its dielectric and ferroelectric behavior. Scanning electron microscopy (SEM) coupled with energy-dispersive X-ray spectroscopy (EDX) showed that particle size increased from 3.04 μm to 12.16 μm with sintering temperature. The dielectric properties of the ceramic compounds were investigated over a broad frequency and temperature range. The maximum dielectric constant (εrmax) reached 41554 at 1300 °C and 1 kHz. The samples demonstrated a diffuse ferroelectric behavior, with this effect becoming less prominent at higher sintering temperatures. These results suggest that (1-x)LaFeO₃-xBaTiO₃ compositions with x = 0.49 exhibit promising structural and dielectric properties for advanced ferroelectric device applications.